PENAKLUKAN RUANG PUBLIK OLEH KUASA AGAMA - Sofia Hayati (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
SARA conflict adorns the life of the Indonesian people in recent years. The tendency of each community group to emphasize their respective identities, both cultural and religious identity. The phenomenon of mastering public space by certain religious identities was found in the Special Region of Yogyakarta, precisely in the village of Sengkan, Desa Condongcatur, Sleman. In this village, the names of the streets were found with the nuances of city names written in the Bible. In conducting this study, the author examines how the impact of the emergence of certain religious identities in public space, as well as how the role of community leaders in creating consensus in the public space. This paper was analyzed using discourse theory and consensus of Jürgen Habermas. The concept of Habermas's public space is a space for critical discussion and is open to everyone. What discourse theory wants to show is not the purpose of society, but only the way or procedure to achieve the goal. Rationality is the method used in accepting consensus. As for the impact of the emergence of certain religious identities in the public sphere, namely protests from some minority (Muslim) communities that gave rise to conflict which resulted in residents asking to replace street names with more general names, without any tendency of any religious identity. In addition, the difficulties of Muslims in establishing places of worship and inconvenience of minorities towards their environment. The role of community leaders in creating consensus in the public sphere, namely community leaders who are there have a dual function, so that they can facilitate the purpose of naming the road and reducing community protests so that consensus is premature or fails because there is no awareness of accepting all citizens